Description of the leg movements of infants in an aquatic environment - Wielki, C.; Houben, M. (Biomechanics and Medicine in Swimming, 1983)
The majority of research concerning the mechanics of swimming has been confined to competitive swimming strokes of males and females over the age of 10 yr. With the increased emphasis on teaching children to swim during infancy, there is a need to investigate infants' swimming patterns. The purpose of this study, therefore, was to describe the movement patterns for the lower limbs of infants aged 3-20 months as they propelled themselves in the water under different support conditions. It was felt that this might provide a greater understanding of the natural evolution of aquatic movement patterns and help in developing guidelines for manipulation of the learning environment (Wielki, 1980).